Evaluasi Kompetensi Guru IPS dalam Menerapkan Model Pembelajaran Berbasis Kearifan Lokal di Sekolah Dasar - Putri Suci Rahmadani Br Sinurat; Nabilla Nabilla; Nabila Arbaa Fadhilah (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to evaluate the competence of fourth-grade social studies teachers in implementing a local wisdom-based learning model in elementary schools. The method employed is a literature review with a qualitative approach, analyzing various relevant scholarly sources. The findings reveal that the success of implementing this learning model is influenced by mastery of local wisdom content, contextual teaching strategies, active student engagement, and comprehensive evaluation practices. Teachers with deep understanding of local culture and the ability to design lessons relevant to students' lives are more effective in shaping character education. These results highlight the importance of teacher training and professional development to enhance competence in integrating local values into social studies instruction.